A Comparative Study between Operating Systems (Os) for the Internet of Things (IoT) - Hicham, Aberbach; Sabri, Abdelouahed; Jeghal, Adil; Tairi, Hamid (Transactions on Engineering and Computing Sciences, 2017)
<!--[if gte mso 9]> Normal 0 false false false FR X-NONE AR-SA <![endif]--> We describe The Internet of Things (IoT) as a network of physical objects or "things" embedded with electronics, software, sensors, and network connectivity, which enables these objects to collect and exchange data in real time with the outside world. It therefore assumes an operating system (OS) which is considered as an unavoidable point for good communication between all devices “objects”. For this purpose, this paper presents a comparative study between the popular known operating systems for internet of things . In a first step we will define in detail the advantages and disadvantages of each one , then another part of Interpretation is developed, in order to analyse the specific requirements that an OS should satisfy to be used and determine the most appropriate .This work will solve the problem of choice of operating system suitable for the Internet of things in order to incorporate it within our research team . <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false FR X-NONE AR-SA <![endif]--> We describe The Internet of Things (IoT) as a network of physical objects or "things" embedded with electronics, software, sensors, and network connectivity, which enables these objects to collect and exchange data in real time with the outside world. It therefore assumes an operating system (OS) which is considered as an unavoidable point for good communication between all devices “objects”. For this purpose, this paper presents a comparative study between the popular known operating systems for internet of things . In a first step we will define in detail the advantages and disadvantages of each one , then another part of Interpretation is developed, in order to analyse the specific requirements that an OS should satisfy to be used and determine the most appropriate .This work will solve the problem of choice of operating system suitable for the Internet of things in order to incorporate it within our research team . Keywords: Internet of things , network, physical object ,sensors,operating system.